Formulation and evaluation of loratadine mouth dissolving tablet (Bangladesh Journal of Scientific and Industrial Research, 2013)
Loratadine 10 mg mouth dissolving tablet (MDT) was prepared by using super disintegrant such as sodium starch glycollate, crosscarmellose sodium, crospovidone at various concentration, aspartame was used as sweetening agent. The excipients were used for this study was based on the compatibillity studies. All the formulation was prepared by direct compression method. Among all the formulations crospovidone at 10 mg/tab gives 99.1% drug release at end of 12th min. It was considered as optimized batch. The optimized batch was processed for all the evaluation parameter and stability studies. The final formulations were packed in blister package. Bangladesh J. Sci. Ind. Res. 48(2), 137-142, 2013 DOI: http://dx.doi.org/10.3329/bjsir.v48i2.15745